2015
DOI: 10.2112/jcoastres-d-14-00010.1
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variability of Two Offshore Sand Banks in a Region of Extreme Tidal Range

Abstract: Lewis, M.J.; Neill, S.P., and Elliott, A.J., 2015. Interannual variability of two offshore sand banks in a region of extreme tidal range. Journal of Coastal Research, 31(2), [265][266][267][268][269][270][271][272][273][274][275], ISSN 0749-0208.Offshore sand banks play important roles for coastal flood protection and fisheries, and they are sources of marine aggregates. An 11-year record (1991An 11-year record ( -2002 of annual bathymetric surveys from two sand banks (Nash and Helwick) in the Bristol Channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…A greater question is the impact of waves on sediment transport over these sandbanks, which were not included in these simulations. Studies conducted on offshore sandbanks on the south Wales coast [69] have suggested that sandbank volume changes are primarily related to storm conditions. Waves were not included in this contribution given the vast number of permutations of possible wave conditions that would need to be tested, however future work should consider this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…A greater question is the impact of waves on sediment transport over these sandbanks, which were not included in these simulations. Studies conducted on offshore sandbanks on the south Wales coast [69] have suggested that sandbank volume changes are primarily related to storm conditions. Waves were not included in this contribution given the vast number of permutations of possible wave conditions that would need to be tested, however future work should consider this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Waves can have a significant contribution to sediment dynamics in shelf sea regions (e.g., van der Molen, 2002;Wiberg et al, 2002) by inducing a stirring mechanism into the hydrodynamic system, thus keeping the sediment suspended and susceptible to net transport by tidal currents. Waves are the primary mechanism for inter-annual variability in sediment transport due to sensitivity to variability in atmospheric (wind) forcing (Lewis et al, 2014a). In shallower, inshore areas of the Irish Sea, nearshore wave effects become more important than tidal-induced currents for transporting sediments.…”
Section: Limitations Of the Gstcpmentioning
confidence: 99%
“…Ref. [12]). Detailed analysis revealed no strong linear relationship between tidal current misalignment and water depth (R 2 regression score below 1%), or between tidal current misalignment and peak tidal velocity (R 2 regression score of 6%); however it appears more likely that flow will be rectilinear in deeper water and in lower flow tidal energy sites (especially at sites where spring tidal flows are below 2.3 m/s); see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…land based) amphidromes (regions of near-zero tidal range, but strong tidal currents); one around northeast Ireland and a second around southeast Ireland [16,17]. The bathymetry of the Bristol Channel is such that the tide in this region is close to a resonant standing wave, which results in relatively strong tidal currents, and one of the highest tidal ranges in the world [12]. Further, the high tidal ranges in the Eastern Irish Sea induce strong flow past/through bathymetric constrictions such as headlands and islands, and such regions offer attractive resources for tidal energy generation projects (e.g.…”
Section: Case Study: the Irish Seamentioning
confidence: 99%